POLITICS OF BUSINESS LICENSING IN INDONESIA: Involvement of Community Consent in Building Approval - Nurhayati, Nunik; Dimyati, Khudzaifah; Absori, Absori; Wardiono, Kelik (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This article aims to discuss the urgency of community consent and involvement in development in the era of the Job Creation Law in Indonesia. Whereas, The Job Creation Law is designed to reduce the complexity and time needed to obtain permits with the aim of ease of doing business. The impact of this policy is to eliminate community consent in building approvals as one of the basic requirements for business licensing. This research uses normative legal research methods with a statutory approach. The data analysis technique uses descriptive analysis by describing general things to specific ones by describing current business licensing policies in Indonesia to provide general ease of doing business. The results of the discussion showed that community involvement in the building approval process is an important aspect that needs to be considered in the context of the Job Creation Law in Indonesia. Community involvement can be in the form of a public consultation process, where the building owners must obtain approval or at least discuss development plans with the surrounding community to ensure that the project does not harm the interests and lives of the local communities. Looking at the process of forming and amending the Job Creation Law, where there are many community rejections and low levels of participation, it can be seen that the legal politics of the Job Creation Law belongs to an authoritarian political configuration whose legal product character is conservative. This includes the substance of the regulation, which eliminates the requirement for community consent in managing Building Approval.Keywords:Law, Job Creation, Business License, Politics